2022
DOI: 10.4103/jmss.jmss_49_20
|View full text |Cite
|
Sign up to set email alerts
|

Using marker-controlled watershed transform to detect Baker's cyst in magnetic resonance imaging images: A pilot study

Abstract: Nowadays, magnetic resonance imaging (MRI) has a high ability to distinguish between soft tissues because of high spatial resolution. Image processing is extensively used to extract clinical data from imaging modalities. In the medical image processing field, the knee's cyst (especially Baker) segmentation is one of the novel research areas. There are different methods for image segmentation. In this paper, the mathematical operation of the watershed algorithm is utilized by MATLAB software based on marker-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) is one of the most crucial, extensively utilized, and powerful imaging modalities that ofer numerous advantages, such as high spatial resolution, unrestricted tissue depth penetration, multiplanar imaging, and soft tissue functionality [13][14][15]. MRI has been used in various medical aspects and biomedical applications, including diagnosis, therapy, follow-up, and treatment assessment; cancer imaging; infammation detection and perfusion imaging; and targeted MRI-guided drug delivery, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is one of the most crucial, extensively utilized, and powerful imaging modalities that ofer numerous advantages, such as high spatial resolution, unrestricted tissue depth penetration, multiplanar imaging, and soft tissue functionality [13][14][15]. MRI has been used in various medical aspects and biomedical applications, including diagnosis, therapy, follow-up, and treatment assessment; cancer imaging; infammation detection and perfusion imaging; and targeted MRI-guided drug delivery, among others.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] The high signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), spatial resolution, contrast resolution and the abundance of MRI sequences available to define intracranial lesions allow MRI to give more detailed, localisation and characterisation of BMs. 16,17 To be more specific, T1-weighted (T1-w) and T2-weighted (T2-w) sequences outline the morphologic and anatomical de-alignment of tissue brought about by the tumour. 18 The purpose of this systematic review was to document the utility of reported MRI techniques in imaging BC, as well as the MRI and clinical features of BMs from BC to aid in the diagnosis and treatment of similar individuals in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) scans and magnetic resonance imaging (MRI) scans are the most common imaging techniques used to diagnose brain malignancies 10–15 . The high signal‐to‐noise ratio (SNR), contrast‐to‐noise ratio (CNR), spatial resolution, contrast resolution and the abundance of MRI sequences available to define intracranial lesions allow MRI to give more detailed, localisation and characterisation of BMs 16,17 . To be more specific, T1‐weighted (T1‐w) and T2‐weighted (T2‐w) sequences outline the morphologic and anatomical de‐alignment of tissue brought about by the tumour 18 …”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is a noninvasive and novel imaging modality [4][5][6]. The use of contrast agents (CAs) in MRI is offered to enhance image contrast as well as the identification of diseased cells [7].…”
Section: Introductionmentioning
confidence: 99%